Sacred sustainability as a post-development ethos: Recontextualizing Seyyed Hossein Nasr's metaphysics for Indonesia’s ecological crisis - Santono, Agung Nugroho Reformis; Ulva, Maria; Idlofi; Aji, Kurniawan Seno (Journal of Critical Ecology, 2026)
Background: The contemporary ecological crisis in Indonesia reflects not only a failure of governance but a deeper metaphysical rupture caused by the dominance of anthropocentric and extractive development models. While existing literature has extensively discussed Islamic environmental ethics or Seyyed Hossein Nasr’s eco-spirituality separately, there is a scarcity of studies that critically bridge Nasr’s metaphysical traditionalism with modern structural critiques to address the specific political-economic context of Indonesia. This study aims to fill this gap by formulating a "Sacred Sustainability" framework that integrates Qur’anic theocentrism with critical social theory to offer a holistic solution to Indonesia’s environmental degradation. Methods: The study employs a qualitative library research approach, utilizing philosophical hermeneutics to interpret texts. The analytical framework synthesizes Seyyed Hossein Nasr’s philosophia perennis with Jürgen Habermas’s theory of communicative action and Arturo Escobar’s post-development theory. Data were analyzed using an interactive model involving condensation, display, and verification to reconstruct a relevant ethical model. Findings: The research finds that while Nasr’s concepts of Tawḥīd (unity), Khalīfah (stewardship), and Mīzān (balance) provide a strong ontological basis for restoring the sanctity of nature, they lack the political instrumentality to challenge the structural dominance of oligarchy and capitalism in Indonesia. By integrating Critical Theory, this study operationalizes Nasr’s metaphysics into a "Sacred Sustainability" paradigm that not only demands spiritual restoration but also structural transformation through deliberative ethics and the decolonization of development policies. Conclusion: Addressing Indonesia's ecological crisis requires a paradigm shift from material accumulation to spiritual responsibility, positioning environmental preservation as both an ethical obligation and a devotional act. Novelty/Originality of this article: The novelty of this research lies in its unique theoretical synthesis that bridges the gap between Traditionalist Islamic metaphysics and modern Critical Theory (Post-development). It creates a new, contextually grounded framework of "Sacred Sustainability" that transcends the dichotomy between spiritual normativity and socio-political praxis.